2021
DOI: 10.5586/asbp.905
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and Simplification of Aquatic Vegetation Structure and Reoligotrophication of a Lake During the Last 40 Years

Abstract: The recovery or reconstruction of aquatic vegetation has recently been reported as a result of water quality improvement after anthropogenic eutrophication. The objectives of this study were: to investigate long-term trends in aquatic vegetation abundance in relation to decreasing water fertility and to present new directions in changes of the submerged aquatic vegetation structure, species richness, and biodiversity in Lake Kuźnickie (western Poland) with the perspective of the last 40 years (1978–2018). Lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…On the contrary, as shown in the study in Lake Constance, abundant recovery of N. obtusa was observed along with re-oligotrophication of water (Murphy et al, 2018). Our research in Lake Kuźnickie (W Poland), in which N. obtusa is one of co-dominants of the lake submerged vegetation (Brzozowski et al, 2018), also revealed that the increasing share of N. obtusa in submerged vegetation and the spread of this macroalga in the form of monospecific beds coincided with a decrease in total phosphorus concentration and water quality improvement (Brzozowski et al, 2021). Co-occurrence of N. obtusa with aquatic macrophytes across environmental conditions and the native and invaded geographical range Taking into account the predictability and unpredictability of threats to local biodiversity resulting from the expansion of N. obtusa in the area where it is an invasive alien species, and changes in its distribution within the native range (Alix et al, 2017;Karol & Sleith, 2017;Larkin et al, 2018), it seems important to recognize which species may and most often coexist with the charophyte studied under certain environmental conditions.…”
Section: Discussionsupporting
confidence: 54%
“…On the contrary, as shown in the study in Lake Constance, abundant recovery of N. obtusa was observed along with re-oligotrophication of water (Murphy et al, 2018). Our research in Lake Kuźnickie (W Poland), in which N. obtusa is one of co-dominants of the lake submerged vegetation (Brzozowski et al, 2018), also revealed that the increasing share of N. obtusa in submerged vegetation and the spread of this macroalga in the form of monospecific beds coincided with a decrease in total phosphorus concentration and water quality improvement (Brzozowski et al, 2021). Co-occurrence of N. obtusa with aquatic macrophytes across environmental conditions and the native and invaded geographical range Taking into account the predictability and unpredictability of threats to local biodiversity resulting from the expansion of N. obtusa in the area where it is an invasive alien species, and changes in its distribution within the native range (Alix et al, 2017;Karol & Sleith, 2017;Larkin et al, 2018), it seems important to recognize which species may and most often coexist with the charophyte studied under certain environmental conditions.…”
Section: Discussionsupporting
confidence: 54%
“…Desvaux) J. Groves. The lake water quality has improved in recent years, with the lake now classified as mesotrophic (Brzozowski & Pełechaty, 2020; Brzozowski et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the literature (Raabe et al, 2012; Sinkevičienė & Urbaitė‐Maževič, 2012; Karol et al, 2017) and our observations (Pełechaty, Brzozowski & Pietruczuk, 2017), a research hypothesis was formulated: that environmental changes related to global warming provide a competitive advantage to the endangered and indicatory L. barbatus , favouring its spread and expansion in the littoral regions of lakes in temperate climatic zones. The present study was conducted in Lake Kuźnickie that currently hosts one of the most abundant and well‐developed populations of L. barbatus (Brzozowski et al, 2019; Brzozowski et al, 2021). The hypothesis was verified by reconstructing the history of L. barbatus in this model lake by applying an analysis of macroremains in the dated lake sediment cores in the context of climate and lake catchment changes.…”
Section: Introductionmentioning
confidence: 99%
“…Проте відзначався різними дослідниками як в оліготрофних, так і у високоевтрофних водоймах. Популяції нечисленні (Brzozowski et al, 2021).…”
Section: Paludicola Keratophytaunclassified